Pendidikan Agama Kristen Bagi Pemuda Yang Terjerat Kasus Senjata Tajam di Jemaat Gmim Musafir Pinokalan Wilayah Bitung Lima - Mutahang, Marshel Victory; Kalalo, Jefry (UPT Penelitian Fakultas Teologi Universitas Kristen Indonesia Tomohon, 2021)
This research discusses Christian religious education for young people who were involved in cases of sharp weapons in the Gmim Musafir Pinokalan congregation. Christian religious education is education to develop christian personalities ini young people, espacially for youmh people involeved in the sajam case. The Christian Religious education taught will have a positive impact on the youth they guide, because with the presence of Christian religious Education material, the youth’s personality will be formed. The importance of Christian Religious Edcation for the behavior and personality of young people is that it is a means of charater fermation that guides and manages the lives of young people to be able to overcome various problems that can only harm themselves, their families, the church and society.